Criminal Law Enforcement Against Ding Dong Gambling and Fishing in Hamlet II, Sumberingin Village, Namo Bintang Village, Pancur Batu District, Deli Serdang Regency, North Sumatra Province (Analysis of Decision Number 1311/Pid.B/2020/PN.Mdn) - Habibullah Nasution; Khalid (Warmadewa Press, 2024)
Criminal Law Enforcement Against Gambling and Fishing in Hamlet II, Sumberingin Village, Namo Bintang Village, Pancur Batu District, Deli Serdang Regency, North Sumatra Province (Analysis of Decision Number 1311/Pid.B/2020/PN.Mdn). Gambling is a harmful activity that many people engage in. This is one of the crimes that is classified as forbidden by law or religion. Nonetheless, the community as a whole engages in this behavior frequently because they believe that winning this gambling game will double their earnings. Numerous prohibited behaviors exist, ranging in size from little to vast, deliberate or inadvertent, and motivated by genuine whims or practical pranks. Regardless of age, gambling is becoming more and more commonplace. This researcher applies a particular kind of normative legislation. The study methodology known as the normative legal research technique is centered on the examination of primary and secondary sources as well as literature. Both a conceptual approach and a legislative approach are employed in this study. Scholars' perspectives provided the key data for this investigation. Secondary data on this study topic was gathered in the interim from relevant books, papers, journals, and laws. The Medan District Court stressed in its ruling that gambling activities, including fish shooting and ding dong gaming, were illegal based on its review of judgment Number 1311/Pid.B/2020/PN.Mdn. This ruling is a reflection of the rigorous efforts made by law enforcement to implement the rules against gambling-related offenses, which are forbidden under the Law of the Republic of Indonesia. Gambling criminals may face jail time or fines as part of their criminal penalties.